2008
DOI: 10.1097/ta.0b013e31818c8e8c
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response After Extremity or Truncal Fracture Operations

Abstract: The release of proinflammatory cytokines was higher in patients when their pelvic fractures were operated than in patients with spine fracture fixations, and was associated with the degree of blood loss. A higher increase in cytokine levels occurred when they were performed early (day 1-2) across all patient groups. The level of the released markers seems to be related to the magnitude of surgery, rather than to the duration of the procedure. This study supports the value of immunologic markers in determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…Most authors agree that patients in severe traumatic-hemorrhagic shock from bleeding pelvic ring disruptions are unlikely candidates for early definitive pelvic fracture fixation, due to the inherent risk of increased mortality from exsanguinating hemorrhage and the “lethal triad” of coagulopathy, acidosis and hypothermia [22, 146]. A prospective multicenter cohort study revealed a significantly increased extent of blood loss and increased interleukin (IL-6 and IL-8) serum levels, reflective of an exacerbated systemic inflammatory response, in politrauma patients who underwent early pelvic fracture fixation on the first or second day post injury [147]. The early timing and short duration of initial pelvic stabilization revealed to have a positive impact on decreasing the incidence of multiple organ failure (MOF) and mortality [148].…”
Section: Methodsmentioning
confidence: 99%
“…Most authors agree that patients in severe traumatic-hemorrhagic shock from bleeding pelvic ring disruptions are unlikely candidates for early definitive pelvic fracture fixation, due to the inherent risk of increased mortality from exsanguinating hemorrhage and the “lethal triad” of coagulopathy, acidosis and hypothermia [22, 146]. A prospective multicenter cohort study revealed a significantly increased extent of blood loss and increased interleukin (IL-6 and IL-8) serum levels, reflective of an exacerbated systemic inflammatory response, in politrauma patients who underwent early pelvic fracture fixation on the first or second day post injury [147]. The early timing and short duration of initial pelvic stabilization revealed to have a positive impact on decreasing the incidence of multiple organ failure (MOF) and mortality [148].…”
Section: Methodsmentioning
confidence: 99%
“…Although numerous basic science studies in orthopedics have suggested that orthopedic trauma injuries may be associated with immune responses that facilitate sepsis [1518], it is currently unclear whether orthopedic trauma patients are at increased risk for developing sepsis or septic shock. Existing studies have correlated trauma to large groups of adverse events, making it difficult to extrapolate associations to septic complications [19–22]. However, the relationship between sepsis and high mortality, its enormous financial costs, and the increasing emphasis on quality metrics make it imperative that orthopedic surgeons are able to identify trauma patients who may be more likely to develop the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim was to mimic severe trauma from a large long bone (femur) fracture, in which soft tissue injury and the release of bone components are present at the same time. We induced fibula fracture to simulate the stress of long bone fracture, but unlike a femur fracture, this manipulation does not necessitate fixation surgery that could exacerbate outcomes (37,39). Because the fibula is very small, we injected additional bone components to the injured area as described in previous studies (35, 36a, 48).…”
Section: Severe Orthopedic Trauma Protocolsmentioning
confidence: 99%